(untitled) (Raparin Journal of Humanities (RJH), 2023)
When the world of economy developed, various reports have been written and published via TVs, radios, websites and the like. The writers of economic news mostly use abstract concepts which usually seem boring and misinterpreted by ordinary people. To make them interested in such news, figurative language is manipulated. One of these rhetorical devices dominantly used in this genre is conceptual metaphor (CM) which is regarded as a vehicle in perceiving the world around us. The present study highlights its salient roles and implications in selected English economic news reports. It aims to identify, analyze, qualify and quantify the patterns of conceptual metaphor: structural, ontological and orientaional, adopted in English economic news reports. To do so, three economic news reports have been selected from Mail Online and U.S. News. The former is a news website in the United Kingdom and the latter is a news website in the USA. The data have been chosen randomly for each type of conceptual metaphor and have been analysed accordingly. The results indicate that the most dominant pattern of conceptual metaphor is a structural metaphor and the least frequent is an orientational one.